The role of GATA2 in adult hematopoiesis and cell fate determination - Peters, Iris J. A.; de Pater, Emma; Zhang, Wei (Frontiers in Cell and Developmental Biology, 2023)
The correct maintenance and differentiation of hematopoietic stem cells (HSC) in bone marrow is vital for the maintenance and operation of the human blood system. GATA2 plays a critical role in the maintenance of HSCs and the specification of HSCs into the different hematopoietic lineages, highlighted by the various defects observed in patients with heterozygous mutations in GATA2, resulting in cytopenias, bone marrow failure and increased chance of myeloid malignancy, termed GATA2 deficiency syndrome. Despite this, the mechanisms underlying GATA2 deficiency syndrome remain to be elucidated. The detailed description of how GATA2 regulates HSC maintenance and blood lineage determination is crucial to unravel the pathogenesis of GATA2 deficiency syndrome. In this review, we summarize current advances in elucidating the role of GATA2 in hematopoietic cell fate determination and discuss the challenges of modeling GATA2 deficiency syndrome.